(untitled) (PerCursos, 2021)
This essay addresses the different ways in which Latin American documentary cinema has sought to translate the continent’s social dilemmas. Through films made on the continent in the last 60 years, we approach some of the main schools and ways of making documentaries, such as the expository documentary, the Brazilian sociological model, the third cinema, the subjective turn and the film essay. We seek to point out the origins of the different strategies (both cinematographic and social) in dissimilar social settings, historical circumstances, and the new possibilities of displacement and registration provided by the advent of new technologies.